Skinfold reference curves and their use in predicting metabolic syndrome risk in children - Alynne C.R. Andaki; Teresa M.B. de Quadros; Alex P. Gordia; Jorge Mota; Adelson L.A. Tinôco; Edmar L. Mendes (Elsevier, 2017)
Objectives: To draw skinfold (SF) reference curves (subscapular, suprailiac, biceps, triceps) and to determine SF cutoff points for predicting the risk of metabolic syndrome (MetS) in children aged 6-10 years old. Methods: This was a cross-sectional study with a random sample of 1480 children aged 6-10 years old, 52.2% females, from public and private schools located in the urban and rural areas of the municipality of Uberaba (MG). Anthropometry, blood pressure, and fasting blood samples were taken at school, following specific protocols. The LMS method was used to draw the reference curves and ROC curve analysis to determine the accuracy and cutoff points for the evaluated skinfolds. Results: The four SF evaluated (subscapular, suprailiac, biceps, and triceps) and their sum (∑4SF) were accurate in predicting MetS for both girls and boys. Additionally, cutoffs have been proposed and percentile curves (p5, p10, p25, p50, p75, p90, and p95) were outlined for the four SF and ∑4SF, for both genders. Conclusion: SF measurements were accurate in predicting metabolic syndrome in children aged 6-10 years old. Age- and gender-specific smoothed percentiles curves of SF provide a reference for the detection of risk for MetS in children. Resumo: Objetivos: Desenhar curvas de referência de quatro dobras cutâneas (subescapular, suprailíaca, bíceps, tríceps) e determinar pontos de corte para predizer o risco de SM em crianças de seis a 10 anos de idade. Métodos: Estudo epidemiológico de base populacional, corte transversal, com amostra probabilística, estratificada por segmento de ensino, com 1.480 crianças de 6 a 10 anos de idade, 52,2% do sexo feminino, oriundas de escolas públicas e privadas, localizadas na zona urbana e rural do município de Uberaba (MG). Antropometria (dobras cutâneas), pressão arterial e as coletas de sangue em jejum foram realizadas em espaço reservado na escola, seguindo protocolos específicos. O métodolo LMS foi utilizado para desenhar as curvas de referência e análise de curva ROC para determinar a acurácia e pontos de corte para as dobras cutâneas avaliadas. Resultados: As quatro DC avaliadas (subescapular, suprailíaca, bíceps e tríceps) e o seu somatório (∑4DC) foram acurados na predição da SM para meninas e meninos. Adicionalmente, pontos de corte foram propostos e curvas percentílicas (p5, p10, p25, p50, p75, p90 e p95) foram delineadas para as quatro DC e o ∑4DC, para ambos os sexos. Conclusão: Medidas de DC foram acuradas em predizer SM em escolares de seis a 10 anos de idade. As curvas percentílicas de DC desenhadas por idade e sexo fornecem referência na detecção do risco de SM em crianças. Keywords: Anthropometry, Metabolic syndrome X, Cross-sectional studies, Child, Palavras-chave: Antropometria, Síndrome X, Estudos de corte transversal, Crianças